Techno economic analysis of stand-alone hybrid renewable energy system / Hanieh Borhanazad - Hanieh, Borhanazad (2013)
Decentralized electricity generation by renewable energy sources is considered as a solution for remote area’s electrification. However, intermittent nature of these sources leads to develop sizing rules and use hybrid systems to exploit them. This study proposes an integrated PV/wind hybrid system, with battery storage and diesel generator as a backup. Optimization method utilizes the iterative optimization technique following the loss of power probability and the cost of electricity for power reliability and system costs. The optimal size of hybrid energy conversion system founded in this study can be performed technically and economically according to the system reliability requirements. In addition, a sensitivity analysis was carried out on the PV contribution as the most important parameters influencing the economic performances of the hybrid system. This investigation is executed as a techno-economic analysis to design an optimum autonomous hybrid PV-wind-diesel-battery system to meet the load in remote areas of Malaysia The hybrid system with 56-61% of photovoltaic energy penetration combined with wind turbines, diesel generator with a rated power, and storage batteries was found to be an optimal system and economically feasible one.